ChemInform Abstract: Promotion of 1, 3‐Dipolar Cycloaddition Between Azides and β‐Enaminones by Deep Eutectic Solvents. Issue 48 (10th November 2016) - Pinto Martins, Marcos Antonio; Caneppele Paveglio, Guilherme; Valvassori Rodrigues, Leticia; Piccinin Frizzo, Clarissa; Zanatta, Nilo; Bonacorso, Helio Gauze
Abstract: The 1, 3‐dipolar cycloaddition between azides and β‐enaminones to afford triazole derivatives of type (III) is performed using the deep eutectic solvent choline chloride/ethylene glycol (1:2) as solvent.